THE EFFECT COMMUNITY DEVELOPMENT ON CORPORATE IMAGE - Ida Nuryana (Jurnal Manajemen dan Profesional, 2023)
The purpose of this research is to find out; 1) MISYKAT Program Activities Community Development) of Dompet Cares Ummat Daarut Tauhiid Branch (DPU DT) East Priangan to the surrounding areas in carrying out activities; 2) The impact of that activities are shown increase the Corporate Image; 3) The influence of Community Development on Corporate Image. The method of the research used is survey method. The data collection are: : 1) Questionnaire, to obtain primary data; 2) Library research to get secondary data. Sampling method using accidhental. The number of samples was 57 respondents from a population of 132 people, coming from urban and district communities Tasikmalaya became a parnper of the Misykat DPU DT East Priangan Branch. The conclusion of this study states that community development activites have been going well. Keyword: Corporate Image, Community development and Program Misykat. The purpose of this research is to find out; 1) MISYKAT Program Activities Community Development) of Dompet Cares Ummat Daarut Tauhiid Branch (DPU DT) East Priangan to the surrounding areas in carrying out activities; 2) The impact of that activities are shown increase the Corporate Image; 3) The influence of Community Development on Corporate Image. The method of the research used is survey method. The data collection are: : 1) Questionnaire, to obtain primary data; 2) Library research to get secondary data. Sampling method using accidhental. The number of samples was 57 respondents from a population of 132 people, coming from urban and district communities Tasikmalaya became a parnper of the Misykat DPU DT East Priangan Branch. The conclusion of this study states that community development activites have been going well. Keyword: Corporate Image, Community development and Program Misykat.